Pembuatan Karakter Animasi “Halo Saya Disabilitas” untuk Memperkuat Isu Disabilitas pada Sektor Pendidikan - Hadiprawiro, Yulianto; Susanti, Dewi Indah; Hidayati, Atiek Nur; Saptodewo, Febrianto; Dawami, Angga Kusuma (PT. Lancar Media Komunikasi, 2023)
The issue of disability in the education sector still has not had much influence on changing the stigma towards Children with Special Needs (ABK) with disabilities in the education sector. Through the animated characters in the service